Journal Economics, business & accountancy : THE INFLUENTIAL FACTORS ON THE PATIENTS SATISFACTION AND INTENT TO BEHAVE: A CASE STUDY IN NORTH SULAWESI PROVINCE - Lefina Mandey, Silvya (PPPM Perbanas, 2013)
The research analyses the effect of service quality on the hospital’s patients satisfaction and patientsintent to behave, the effect of intent to behave, medical team behavior on patients satisfaction andpatients intent to behave, the effect of communication quality on patients satisfaction and patient intentto behave, patient’s trust on the intent to behave, and patient satisfaction on the intent to behave.The sample consists of whole patients who had been undergoing normal treatment at the hospital attheir own health insurance service or ASKES, in the North Sulawesi province